1992
DOI: 10.1111/j.1365-2621.1992.tb08088.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Pigments of Sweet Potatoes–Ipomoea batatas

Abstract: The anthocyanin pigments of red sweet potato roots (Impomoea batatas) were isolated, purified and identified by HPLC and conventional paper chromatographic, spectral and chemical methods. Two major pigments and two minor pigments were present in fresh tissue slices extracted with boiling 1% HAc methanol. Tissues extracted cold yielded 11 or more pigments probably from degradation of the two major pigments. One major pigment was identified as peonidin-3-diglucoside-5-glucoside with three molecules of ferulic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…Anthocyanins can be degraded by enzyme systems in plant tissues such as glycosidases (anthocyanases), polyphenoloxidases (PPO) and peroxidases (Shi, Bassa, Gabriel & Francis, 1992). Anthocyanin components detected in purple sweetpotato were mainly cyanidin and peonidin glycosides acylated with caffeic acid, ferulic acid and phydroxybenzoic acids, in agreement with previous reports (Suda et al, 2003).…”
Section: Total Phenolics Anthocyanins Phenolic Acids and Ascorbic supporting
confidence: 90%
See 2 more Smart Citations
“…Anthocyanins can be degraded by enzyme systems in plant tissues such as glycosidases (anthocyanases), polyphenoloxidases (PPO) and peroxidases (Shi, Bassa, Gabriel & Francis, 1992). Anthocyanin components detected in purple sweetpotato were mainly cyanidin and peonidin glycosides acylated with caffeic acid, ferulic acid and phydroxybenzoic acids, in agreement with previous reports (Suda et al, 2003).…”
Section: Total Phenolics Anthocyanins Phenolic Acids and Ascorbic supporting
confidence: 90%
“…The increase in caffeic acid content in NCPUR06-020 during storage can be attributed to accumulation of the degradation products of chlorogenic acid, isochlorogenic acid and acylated anthocyanins present in this genotype (Shi et al, 1992). On the other hand, a report by Padda et al (2008) indicated an increase in total phenolic content in cured and non-cured sweetpotato roots after 2 weeks at low storage temperature (5 °C).…”
Section: Total Phenolics Anthocyanins Phenolic Acids and Ascorbic mentioning
confidence: 85%
See 1 more Smart Citation
“…0-coumaric acid was chosen as an internal standard because it does not'occur naturally in these samples. An example of the calculation was reported by Shi et al (1992c).…”
Section: Determination Of the Acyl Groupmentioning
confidence: 99%
“…Shi et al (1992) developed a method based on the ratios of acyl acids to sugars and/or aglycones. That approach was used to confirm identity of the pigments in sweet potatoes, Ipomoea batatas (Shi et al, 1992a) and to help clarify identity of pigments in Tradescanfia pallida (Shi et al 1992a). The latter was reported to contain cyanidin-3,7,3l-triglucoside with three molecules of ferulic acid and a terminal glucose unit as the major pigment.…”
mentioning
confidence: 99%